SCOPE OF INDIVIDUALS WHOSE PROPERTY COULD BE CONFISCATED IN CRIMINAL PROCEEDINGS (World Bulletin of Management and Law, 2022)
This article analyzes the institution of confiscation and the circle of persons whose property will be confiscated based on the norms of criminal and criminal procedure legislation in the course of the implementation of judicial reform. Based on the views and ideas put forward by scientists, the category of persons whose property is subject to confiscation has been scientifically and theoretically investigated. The article carried out a classification according to certain criteria of the category of persons whose property is subject to confiscation in criminal proceedings, by a comparative analysis of the opinions of legal scholars on the category of persons subject to confiscation of property, as well as by considering the concepts in their definitions based on our legislation. According to the results of the analysis, the relevant conclusions are given based on the category of persons whose property will be confiscated in criminal proceedings and their characteristics